Effect of austenitising temperature on austempering kinetics of Ni-Mo alloyed ductile iron - Bosnjak, Branka (Materiali in tehnologije, 2004)
The effect of austenitising temperature on the transformation kinetics of Fe-3.2C-2.68Si-0.07Mn-0.022P-0.003S-0.02Cu-0.12Cr-0.8Ni-0.25Mo mass fractions ductile iron was investigated. X-ray diffraction and optical microscopy were used to determine the transformation kinetics during the austempering at 350 compositumC after austenitising at 850 compositumC and 930 compositumC for 120 min. The stage I reaction of austempering occurs in two steps, first in eutectic cells and than in the intercellular area. Decreasing the austenitising temperature is shown to increase the driving force for the stage I reaction but to have little effect on the stage II reaction. By lower austenitising temperature the rate of transformation is greater, a more uniform microstructure is obtained, while the austemperability is smaller. These changes shift the processing window for Ni-Mo ductile iron for selected austenitising temperature.
Keywords: nodularna litina; avstenitizacija; mikrostruktura